ANALYSIS OF RELIGIOUS NOVEL KERUDUNG DI TITIK API BY MOCH. TAUFIK HIDAYAHTULLAH AS A TEACHING MATERIAL - Hayati, Rini; Arianto, Arianto; Wulandari, Wina (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2022)
The purpose of this study was to determine the religious values ​​contained in the novel Kerudung Di Titik Api by Moch Taufik Hidayahtullah. This novel tells the story of a girl named Cassandra who is educated as a pilgrim graduate from a well-known university in this country. Coming from a family background that thinks God is not a game of options to choose which religion is the best in knowing Him. In the span of time Cassandra reached maturity at the age of two heads, subconscious impulses led her attention to the hijab. He considers this a supernatural invitation that cannot be explained logically and rationally, but the veil in the vortex of Cassandra's life becomes a disaster that throws her into a world of urgency and makes her suffocated by various dialectics. This research uses descriptive analysis method. This method is done by describing the facts which are then followed by analysis. The data analysis technique used is descriptive qualitative because the data requires descriptive explanation. As for this study, the researcher analyzes and discusses the religious values ​​contained in the novel Kerudung Di Titik Api by Moch. Taufik Hidayahtullah the values ​​of faith related to one's belief in Allah SWT, morality related to one's behavior or temperament, and worship related to the relationship that exists between a human being and Allah SWT. Data collection is done by reading and note-taking techniques. From the results of this study, it can be determined that religious values ​​are in the form of values ​​of faith, morals and worship. The values ​​contained in the novel Kerudung Di Titik Api by Moch. Taufik Hidayatullah, namely aqidah there are 21 quotes, morality there are 13 quotes, worship there are 16 quotes.